Strategi Orang Tua dalam Perkembangan Aspek Sosial-Emosi Anak Usia Dini di Masa Pandemi Covid-19 - Nur Azizah; Sarah Busyra (Atta'dib Jurnal Pendidikan Agama Islam, 2021)
The stages of life from birth to death are shaped by the social influences which the person interacts with. In order to develop the social aspects of children, a family role, especially the parents, is needed so that children can develop properly. Social and emotional development are inseparable from one to another. Positive social and emotional development makes it easier for children to get along with others and learn better, as well as in other activities in the social environment. This study aims to determine the strategies taken by parents to develop the socio-emotional aspects of early childhood during the Covid-19 pandemic. The results of this study are that the strategies carried out by parents include providing understanding and education about the pandemic situation, in addition to holding other activities that can be done at home including playing with the mother as practiced by the informants. From the results of interviews, the researcher takes the point that good communication between children and parents, especially by mothers, will make the children easier to understand the conditions for activities that have changed due to the current pandemic. Keywords: parents, strategies, social-emotional, early childhood